2007
DOI: 10.1016/j.mce.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the FSH receptor: New perspectives

Abstract: The cell-surface receptor for the gonadotropin follicle-stimulating hormone (FSH) is expressed exclusively on Sertoli cells of the testis and granulosa cells of the ovary. FSH signal transduction through its receptor (Fshr) is critical for the timing and maintenance of normal gametogenesis in the mammalian gonad. In the 13 years since the gene encoding Fshr was first cloned, the mechanisms controlling its transcription have been extensively examined, but a clear understanding of what drives its unique cell-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 56 publications
(79 reference statements)
0
33
1
Order By: Relevance
“…Recent transgenic analysis of a 413-kb yeast artificial chromosome corroborated the promoter deficiency and added additional support for the importance of distal regulatory regions in Fshr transcription (38). Despite containing a large genomic region with the entire Fshr coding sequence (from 97 kb upstream of exon 1 to 57 kb downstream of exon 10), this transgene failed to express in either Sertoli or granulosa cells (14). Furthermore, like the two previous promoter studies that investigated cellular expression, YAC transgene expression was observed in the testis but only ectopically in germ cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent transgenic analysis of a 413-kb yeast artificial chromosome corroborated the promoter deficiency and added additional support for the importance of distal regulatory regions in Fshr transcription (38). Despite containing a large genomic region with the entire Fshr coding sequence (from 97 kb upstream of exon 1 to 57 kb downstream of exon 10), this transgene failed to express in either Sertoli or granulosa cells (14). Furthermore, like the two previous promoter studies that investigated cellular expression, YAC transgene expression was observed in the testis but only ectopically in germ cells.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to controlling Fshr basal transcription, the E-box and USF were required to convey transcriptional signals that activate Fshr by the orphan nuclear receptor NR5A1, better known as steroidogenic factor 1 (SF-1) (13,15,21). Thus, the E-box, together with USF1 and USF2, likely coordinates Fshr transcription by integrating signals from other transcription factors bound elsewhere on the promoter or to more distal regulatory elements (14).…”
mentioning
confidence: 99%
“…Although the best-known function of Foxp1 is to promote development of the B cell lineage of the immune system (65); it is also expressed in the hypothalamus, in which it functions to increase food intake and body weight, and it is negatively regulated by leptin (66); Usf2 is a member of the evolutionary conserved family of basic-helix-loop-helix-leucine zipper transcription factors (67); recognized by an E-box binding motif present in various gene promoters, it plays an important role in the regulation of gene transcription by recruiting chromatin remodeling enzymes (67). An involvement of Usf2 in the control of reproductive function was recently shown by the finding that Usf2 controls the expression of the FSH receptor gene (68). FSH receptors mediate the actions of the gonadotropin FSH on the hypothalamic-pituitary-gonadal axis.…”
Section: Trg Expression Also Increases In the Rodent Hypothalamus At mentioning
confidence: 99%
“…FSH and its relative, LH, are major components of the hypothalamic-pituitary-gonad axis, which regulates reproductive function and ultimately the production of gametes and fertility [12]. By binding FSH receptor (FSHR) located on the membrane of ovarian granulosa cells, FSH promotes the development of immature follicles, eventually leading to the formation of mature preovulatory follicles [13,14].…”
Section: Introductionmentioning
confidence: 99%